Impact of Accounting Conservatism on Income Smoothing: Empirical Evidence From Algeria - Kimouche, Bilal; Charchafa, Ilyes (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2024)
This paper investigates the impact of accounting conservatism on income smoothing as a proxy for accounting manipulation. The study used 993 observations for 133 Algerian companies from 2012 to 2020, where income smoothing was measured by the variations in cash flows relative to earnings. However, conservatism was measured through non-operating accounting accruals, accruals-to-earnings ratio before extraordinary items, and allowances. The results showed that total accruals do not impact income smoothing versus positive impacts from non-operating accruals and allowances to income smoothing. Therefore, the study concluded that accounting conservatism facilitates income smoothing in Algerian companies by extending the discretionary room available for managers to manipulate earnings. These results require accounting regulators to consider the role of conservatism in manipulation when setting or amending accounting standards. They also imply that auditors should give more attention to conservative accounting practices to limit the opportunistic behavior of managers and increase the reliability of financial information.